2022
DOI: 10.18240/ijo.2022.06.05
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal imaging of experimental choroidal neovascularization

Abstract: AIM: To compare choroidal neovascularization (CNV) lesion measurements obtained by in vivo imaging modalities, with whole mount histological preparations stained with isolectin GS-IB4, using a murine laser-induced CNV model. METHODS: B6N.Cg-Tg(Csf1r-EGFP)1Hume/J heterozygous adult mice were subjected to laser-induced CNV and were monitored by fluorescein angiography (FA), multicolor (MC) fundus imaging and optical coherence tomography angiography (OCTA) at day 14 after CNV induction. Choroidal-retinal pigment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…6,25 We have recently shown that measurement of fluorescein leakage correlates well with CNV measurements ex vivo. 27 Thus, the Heyex software version 1.10.2.0 (Heidelberg Engineering Inc., Franklin, USA) was used for the delineation and measurement of fluorescein leakage areas. Lesions with hemorrhages were excluded from the analysis.…”
Section: In Vivo Imaging and Fluorescein Leakage Measurementsmentioning
confidence: 99%
“…6,25 We have recently shown that measurement of fluorescein leakage correlates well with CNV measurements ex vivo. 27 Thus, the Heyex software version 1.10.2.0 (Heidelberg Engineering Inc., Franklin, USA) was used for the delineation and measurement of fluorescein leakage areas. Lesions with hemorrhages were excluded from the analysis.…”
Section: In Vivo Imaging and Fluorescein Leakage Measurementsmentioning
confidence: 99%